Effects of ketamine and ketamine with midazolam on emergence agitation in children following sevoflurane anesthesia - Sharma, Achyut; Rana, Resham Bahadur (Journal of Society of Anesthesiologists of Nepal, 2018)
Background : Emergence agitation is a distressful phenomenon associated with inhalational agents such as Sevoflurane in short surgical procedures. Various drugs have been used in the past but some come at the cost of increased complications. We aim to study the effects of ketamine alone and ketamine with midazolam on emergence agitation and their effects on recovery and discharge times. Methods: We conducted a prospective randomized controlled trial among 94 patients aged two to ten years presenting for ophthalmic surgeries in which 45 patients were allocated to each group: group K (Ketamine) and group KM (Ketamine with Midazolam). Group K received Ketamine 0.3 mg/kg IV and Group KM received Ketamine 0.3 mg/kg IV and Midazolam 0.03 mg/kg IV. Intraoperatively heart rate and post-operatively emergence agitation, recovery times, discharge times were studied. Results: Demographic variables were comparable between the two groups. Median Pediatric Anesthesia Emergence Delirium (PAED) score of 6 with IQR (4-6) in group K was comparable to the median score of 5 with IQR (4-6) in group KM. The mean recovery time of 22}4.82 min in group K was significantly lower compared to the mean time of 25.75}3.32 min in group KM. Mean time to discharge of 67}11 min from the hospital in group K was significantly shorter compared to that in group KM (108}18 mins). Conclusion: We concluded from our study that ketamine alone is as effective as ketamine with midazolam in reducing the emergence agitation following Sevoflurane anesthesia for ophthalmic surgery. Journal of Society of Anesthesiologists of Nepal Vol. 4, No. 2, 2017, page: 57-65